Deregulating Innovation Capital: The Effects of the JOBS Act on Biotech Startups. Issue 2 (1st December 2022) - Lewis, Craig M; White, Joshua T
Abstract: We examine real outcomes for biotech startups going public around the Jumpstart Our Business Startups (JOBS) Act. Reduced compliance costs associate with greater innovation capital formation as biotech IPO volume and proceeds increase after the JOBS Act. Biotechs, which conduct over 30% of IPOs since 2012, go public with products earlier in the FDA approval process and more frequently target rare diseases and cancer. Consistent with our survey evidence that managers use compliance savings to invest in R&D, we link the JOBS Act to post-IPO increases in project-level development, such as new patents, clinical trials, and staffing of laboratories. Post-JOBS Act product candidates are more likely to reach key milestones in the FDA approval process and these startups fail at lower rates. Benefits accrue to shareholders without sacrificing financial reporting quality. Our results demonstrate how tailoring regulations for startups can provide economic and societal benefits. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.